Strategi Bersaing Stasiun Jaringan NET TV Yogyakarta di Era Digital - Andreas Tri Pamungkas (Program Studi Ilmu Komunikasi, 2022)
Digitalization has given opportunities and threats for new businesses in broadcasting services because it will create a more competitive environment. This research was intended to identify and to analyze NET TV’s strategies in the digital era in winning the competition. This study utilized a descriptive-qualitative method with case strategy approach. The data were analyzed using PEST and Porter’s industry value chain. The results of this research discovered that in order to create a more beneficial economy, NET TV Bureau Yogyakarta optimized digital media such as YouTube and Instagram, the business shake-up provided the private broadcasting station with supporting strength for realizing a network system established based on the democratization of broadcasts.